The Effectiveness of Koran Recitation to Reduce Academic Anxiety Among First Year Students: A Randomized Controlled Trial - Nursyah, Febri Yordan Dwi; Apriliawati, Denisa (Utan Kayu Publishing, 2025)
Academic anxiety, characterized by stress and worry related to evaluation processes, is a significant challenge among first-year students, often leading to poor academic performance. Religious-based interventions, such as Koran recitation, have shown promise as non-pharmacological strategies for managing anxiety. This randomized controlled trial aimed to investigate the impact of Koran recitation on reducing academic anxiety among first-year psychology students at UIN Sunan Kalijaga. A total of 39 participants were purposively selected based on criteria including moderate to high academic anxiety, no use of anti-anxiety medication, and limited memorization of Koranic verses. Participants were divided into three groups: one listened to Ayat As-Sakinah, another to Surah Fussilat, and the control group received no intervention. The Academic Anxiety Scale by Huberty (2012) was used to measure outcomes. Results indicated that listening to Surah Fussilat significantly reduced academic anxiety, while Ayat As-Sakinah also reduced anxiety but not to a statistically significant level. In contrast, the control group experienced an increase in anxiety. These findings underscore the potential of religious-based interventions, particularly Koran recitation, as effective tools to alleviate academic anxiety, offering practical implications for educational institutions seeking culturally relevant and accessible mental health strategies.